The Role of Women in Economic Governance for Sustained and Equitable Growth in the African Continent - Emerson Abraham Jackson (ZBW - Leibniz Information Centre for Economics, 2024)
This paper delves into the vital role of women in economic governance for achieving sustained and equitable growth in Africa. Historically, African women have played significant roles in economic activities and governance structures, particularly in pre-colonial societies, where they were integral to agricultural production, trade, and local governance. However, colonial and post-colonial periods saw a decline in their influence due to imported patriarchal norms. The chapter examines how modern initiatives, such as the African Union's Agenda 2063 and the African Continental Free Trade Area, have aimed to promote economic integration and resilience but still face challenges like corruption, inadequate infrastructure, and socio-political instability. It highlights the importance of gender-inclusive governance, supported by research indicating that including women in leadership leads to better financial performance and more sustainable policy outcomes. Case studies from Rwanda, where women hold 61% of parliamentary seats, and Nigeria, where women like Ngozi Okonjo-Iweala have made significant economic reforms, illustrate the positive impact of female leadership. The chapter also addresses barriers to women's participation, including cultural norms, patriarchal systems, and legal constraints, and suggests policy reforms to enhance gender equality in governance. Philosophical perspectives on equity and justice, particularly those of John Rawls and Martha Nussbaum, are used to argue for the inclusion of women in governance structures. Strategies for enhancing women's roles through education and capacity-building initiatives are discussed, emphasizing the need for comprehensive approaches to gender equality. The chapter concludes by asserting that empowering women in economic governance is not only a matter of fairness but is essential for achieving long-term economic stability and reducing disparities across Africa.
Keywords: J16; O15; P16; D63; 330; Women and Economic Governance; Inclusive and Sustainable Growth; African Continent